Evaluation and identification of advanced lentil interspecific derivatives resulted in the development of early maturing, high yielding, and disease-resistant cultivars under Indian agro-ecological conditions - Singh, Mohar; Kumar, Sanjeev; Mehra, Reena; Sood, Salej; Malhotra, Nikhil; Sinha, Reena; Jamwal, Sonika; Gupta, Vikas (Frontiers in Plant Science, 2022)
The genetic base as revealed by pedigree records of majority of released cultivars appears to be narrow in major pulse crops including lentil, because of frequent use of the same parents and their derivatives in crop improvement programmes. Therefore, corrective measures are needed for widening the genetic base by involving genetic resources of distinct gene pool. In this direction, rigorous efforts were made to introgress wild Lens taxa, L. culinaris ssp. orientalis and L. ervoides into the backgrounds of cultivated varieties. Subsequently, genetic materials were advanced through single seed descent method of breeding along with rapid generation advancement (normal and off-season) approach. Two F10:11 interspecific derivatives of lentil were evaluated in augmented block design at two locations viz. International Centre for Agricultural Research in Dry Areas (ICARDA) and Sher-e-Kashmir University of Agricultural Sciences and Technology (SKUAST), India. The analysis of variance showed remarkable variability for all target characters at both the locations. The heritability estimates were high and correlation analysis exhibited significant association between majority traits assessed at ICARDA and SKUAST, India. Further, SKUAST identified most promising lines named as ‘Jammu Lentil 144’ and ‘Jammu Lentil 71’. These derivatives were further validated separately for their agronomic potential and resistance against major biotic stresses. The results revealed that Jammu Lentil 144 and Jammu Lentil 71 produced 16.65% and 9.40% more seed yield than local and national checks including earliness by 25 days and 15 days, respectively. These promising interspecific derivatives were also found to be resistant against Fusarium wilt, root rot, pod borer and aphid infestations. The standard agronomy of these cultivars has also been assessed consecutively for two years at SKUAST. Overall, the prebreeding efforts have resulted in the development of early maturing, high yielding and disease resistant lentil cultivars for Jammu region of India.